TOLERANCE OF UNCERTAINTY AS A COMPONENT OF THE PROCESS OF LIFE-CREATION OF FUTURE EDUCATORS - Halian, Ihor; Machynska, Natalia; Lozynska, Svitlana; Nos, Liubov; Derkach, Yuliya; Prots, Marta; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose is to present the empirical research on tolerance of uncertainty as a component of future educators’ life-creation process during their studies at higher education institutions. The study emphasizes that intolerance of uncertainty is developed because of inability to act without clearly determined guidelines, intention to receive utmost clarity in ambiguous situations and inclination to avoid uncertainty. The study empirically investigates tolerance of uncertainty as a component of the process of life-long learning of future educators. The results show that intention for self-expression; independence and autonomy are not considered as personal growth by the respondents. Factor analysis allowed establishing the structure of the process of life-creation of future educators, consisting of four main factors (64.21%). The structure factors are: “Psychological well-being” (3.904; 20.55%), “Tolerance of uncertainty” (3.528; 18.57%), “Life awareness” (2.753; 14.49%) and “Selfdevelopment of personality” (2.014; 10.60%). The study determines that the research participants’ consciousness of life awareness is not based on an integral and realistic opinion on it. It recommends that a low level of tolerance should be considered as an incentive to renew life-creation practices